Quantifying disruptive trade policies - Christoph Böhringer; Thomas F. Rutherford; Edward J. Balistreri (University of Oldenburg, Department of Economics, 2018)
Mainstream economic wisdom favoring cooperative free trade is challenged by a wave of disruptive trade policies. In this paper, we provide quantitative evidence concerning the economic impacts of tariffs implemented by the United States in 2018 and the subsequent retaliations by partner countries. Our analysis builds on a multi-region multi-sector general-equilibrium simulation model of the global economy that includes an innovative monopolistic-competition structure of bilateral representative firms.
Keywords: C68; F12; F17; 330; Applied economic analysis; Multi-region models; Trade policy; Monopolistic competition; Trade wars